When teaching and volunteering go together: exploring participation characteristics and demographic backgrounds of senior volunteer teachers and their teaching satisfaction - Leung, D. D. M. (International journal of lifelong education, 2016)
Senior volunteer teachers play important roles in learning programmes for the elderly. These volunteers' level of teaching satisfaction was assumed to influence programmes, their organizational behaviours and outcomes. However, scant research has focused specifically on volunteers' levels of satisfaction with teaching and how their satisfaction is influenced by participation characteristics and their demographic backgrounds. This initial study conducted in Hong Kong attempts to examine this topic. Data from 236 samples from 56 units across the territory were utilized in this study. The results showed that the overall level of teaching satisfaction among senior volunteer teachers was quite high. Senior volunteer teachers with longer teaching experience and teachers with longer service felt satisfied in many areas of teaching. Teachers who taught a greater number of subjects experienced less satisfaction. A 'u-shaped' trend of satisfaction correlated with the number of classes taught; senior volunteer teachers teaching 1-2 classes and volunteers teaching 6 or more classes exhibited higher satisfaction levels in various areas. The number of average teaching hours per week could simultaneously facilitate and hinder different facets of satisfaction. Female teachers experienced higher levels of 'Recognition' than male counterparts. Older senior volunteer teachers were quite satisfied in the areas of 'Working Conditions' and 'Authority'. Findings of multiple regression were discussed.